The Description Neurotherapy in Ischemic Stroke Patients - Fatihah, Anisa Zulfa (Jurnal Surya, 2023)
Introduction: Neuroprotectants are a therapy used to prevent the development of infarction in acute ischemic stroke patients. One approach to neuroprotective therapy is to start early administering neuroprotective agents to patients experiencing acute ischemic stroke. This study aims to describe the pattern of use of neuroprotectant drugs in ischemic stroke patients at RSUD Dr. Soegiri Lamongan.Methods: This research method is a descriptive observational method with a cross-sectional study design. Data collection was carried out retrospectively by searching patient medical records and pharmaceutical installation data for the period June-December 2019.Results: The majority of ischemic stroke patients were female (51.5%), the majority were aged 50-59 years (48.5%), had comorbid hypertension (79.4%) and comorbid DM and hypertension (20.6 %). The neuroprotective drug citicoline was prescribed in 32 patients (33%) and piracetam in 19 ischemic stroke patients (19.6%).Conclusion: The highest use of neuroprotective drugs in ischemic stroke patients at RSUD Dr. Soegiri is a combination of citicoline and piracetam (44.3%%).